Once again on a research school in the library-information science - T. V. Zakharchuk (Библиосфера, 2015)
The article shows changes of the scientific community relation to a research school due to introducing programs to support research schools and their inclusion into the list of criteria for certification of universities and research institutes. A special attention is paid to the library-information sciences. It’s spoken on two centers for studying problems of research schools formation and development in the library-information sciences, which have developed in Novosibirsk and St. Petersburg. The author emphasizes the idea that to characterize research schools it would be important to abandon the understanding of a research school as a team of scientists working in a research unit; not to consider representatives of a research school everybody who has defended thesis under the supervision of this or that scientist; to take the position that a research school is not eternal (some schools appear and collapse, others will emerge). It is noted that to determine the research school existence it’s necessary to develop criteria, which can be mitigated for the library-information scientific cycle compared to generally accepted sciences because of its relative youth, the narrowness of the professional community, etc. Such criteria adopted by the professional community can be the foundation for studying research schools in the library-information science.